URGENCY OF MONOTHEISM EDUCATION IN THE FAMILY ON PANDEMIC PERIOD COVID 19 - Hadis Purba (Universitas Dharmawangsa, 2020)
The COVID 19 epidemic has engulfed this nation and the world throughout 2020, as a mu'min, then it is better to do quarantine or